Dynamics of the passive synchronisation of erbium- and ytterbium-doped fibre Q-switched lasers with a common graphene saturable absorber. (6th June 2019) - Ren, Yangyang; Feng, Ming; Ren, Aibing; Zhang, Kang; Yang, Jie; Sun, Guoqing; Wang, Tianhao; Li, Zhenyao; Li, Yigang; Liu, Zhibo; Song, Feng
Abstract: We have demonstrated a passively synchronized Q -switched erbium- and ytterbium-doped fibre laser by a common graphene saturable absorber (GSA), which generates optical pulses centered at 1530 nm and 1060 nm. The dynamics of the synchronisation of this laser have been studied. In this passively synchronized Q -switched laser, 1530 nm laser pulses affect the transmittance of 1060 nm light through the GSA and induce synchronisation of the two laser pulses. These experimental results have been explained by a simplified theoretical model of the dual-wavelength cross absorption modulation effect of a GSA. With the increase in the pump power, the repetition rate of synchronized pulses varies from 24. 51–39. 85 kHz, and the pulse widths of 1530 nm and 1060 nm vary from 6. 02–2. 41 μ s and from 18. 79–3. 29 μ s, respectively.